ANALISIS KEPUASAN PELANGGAN, KEPERCAYAAN, DAN LOYALITAS PELANGGAN: PERAN VARIABEL PEMODERASI SWITCHING COST - Ari Setiyaningrum (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
The purpose of this study is to examine the effect of customer satisfaction on customer loyalty, the effect of trust on customer loyalty, the effect of switching cost as moderating variable on the relationship between customer satisfaction and customer loyalty, and the effect of switching cost as moderating variable on the relationship between trust and customer loyalty. Products are used as objects of this research are celluler telecommunication service providers. Research conducted by survey through questionaires to 160 students of the Economics Faculty of Unika Atma Jaya. The data shows that customer satisfaction influenced customer loyalty significantly, trust influenced customer loyalty significantly, switching cost does not moderate the relationship between customer satisfaction and customer loyalty, and switching cost does not moderate the relationship between trust and customer loyalty.